The Important Role of Leptin in Modulating the Risk of Dermatological Diseases - Su, Xin; Cheng, Ye; Chang, Dong (Frontiers in Immunology, 2021)
It is an indisputable fact that obesity is associated with a series of health problems. One important hallmark of obesity is excessive accumulation of lipids in the adipocyte, especially triglyceride (TG). Currently, the adipocyte has been considered not only as a huge repository of excess energy in the form of fat but also as an important source of multiple hormones and cytokines called adipokines. In obesity, the adipocyte is dysfunctional with excessive production and secretion of pro-inflammatory adipokines, such as tumor necrosis factor α (TNF-α), interleukin 6 (IL-6), and leptin. On the other hand, accumulating evidence has shown that leptin plays a vital role in stimulating angiogenesis, controlling lipid metabolism, and modulating the production of pro-inflammatory cytokines. Furthermore, the various activities of leptin are related to the wide distribution of leptin receptors. Notably, it has been reported that enhanced leptin levels and dysfunction of the leptin signaling pathway can influence diverse skin diseases. Recently, several studies revealed the roles of leptin in wound healing, the hair cycle, and the pathogenic development of skin diseases, such as psoriasis, lupus erythematosus, and dermatological cancers. However, the exact mechanisms of leptin in modulating the dermatological diseases are still under investigation. Therefore, in the present review, we summarized the regulatory roles of leptin in the pathological progression of diverse diseases of skin and skin appendages. Furthermore, we also provided evidence to elucidate the complicated relationship between leptin and different dermatological diseases, such as systemic lupus erythematosus (SLE), psoriasis, hidradenitis suppurativa, and some skin tumors.